Asian elephants as ecological filters in Sundaic forests - Ong, Lisa; Tan, Wei Harn; Davenport, Lisa C.; McConkey, Kim R.; Mat Amin, Mohamad Khairul Adha bin; Campos-Arceiz, Ahimsa; Terborgh, John W. (Frontiers in Forests and Global Change, 2023)
Megaherbivores exert strong top-down influence on the ecosystems they inhabit, yet little is known about the foraging impacts of Asian elephants (Elephas maximus) on the structure of Southeast Asia’s rainforests. Our goal was to document Asian elephants’ dietary composition, selectivity, and foraging impacts in a Sundaic rainforest and test whether these differed between habitats. We conducted controlled direct observations of five wild-born captive elephants feeding on six plant types (bamboo, grass, monocot herbs, palms, lianas, and trees) of different age 2 in two habitats (mature vs. early successional forest) in Krau, Peninsular Malaysia. Palms, trees, and lianas formed the bulk of the elephants’ diet. In the mature forest, elephants showed a strong preference for monocots (preference ratio, PR = 5.1), particularly large palms (PR = 5.4), while trees were negatively selected (PR = 0.14). Conversely, in early successional habitats, large tree saplings were positively selected (PR = 1.6). Elephants uprooted (30%) and broke the main stem (30%) of the dicot trees, mainly large saplings, that they handled. Tree saplings broken by elephants had an average diameter of 1.7 ± 1.1 cm (up to 7 cm), with breaks happening at 1.1 ± 0.5 m of height. We estimated that, in a year, an elephant could damage (i.e., either uproot or break) around 39,000 tree saplings if it fed entirely in mature forest, and almost double the number (73,000) if it fed solely in early successional habitats. Assuming a density of 0.05–0.18 elephants/km2, elephant foraging could damage 0.2–0.6% of the tree sapling population per year. Slow growth rates of understory plants in mature forests could result in negative feedbacks, whereby elephants suppress palms, other monocots, and highly preferred tree species. Alternatively, elephants may initiate positive feedbacks by impeding succession along forest edges and in semi-open environments, thereby increasing the size of gaps and the availability of their preferred foodplants. Overall, our results show that Asian elephants act as ecological filters by suppressing the plants they prefer in Southeast Asia’s rainforests.